Biological activity of galacto-oligosaccharides: A review - Mei, Zhaojun; Yuan, Jiaqin; Li, Dandan (Frontiers in Microbiology, 2022)
Galacto-oligosaccharides (GOS) are oligosaccharides formed by β-galactosidase transgalactosylation. GOS is an indigestible food component that can pass through the upper gastrointestinal tract relatively intact and ferment in the colon to produce short-chain fatty acids (SCFAs) that further regulate the body's intestinal flora. GOS and other prebiotics are increasingly recognized as useful food tools for regulating the balance of colonic microbiota-human health. GOS performed well compared to other oligosaccharides in regulating gut microbiota, body immunity and food function. This review summarizes the sources, classification, preparation methods, and biological activities of GOS, focusing on the introduction and summary of the effects of GOS on ulcerative colitis (UC), to gain a comprehensive understanding of the application of GOS.